Modern Approaches to the Treatment of Respiratory Distress Syndrome in Children: The Role of Surfactant and Antenatal Prophylaxis - Aisuluu Omurzakova; Venera Azhikulova; Mairamkan Sharipova; Nargiza Kurbanova; Gulnura Zhunusbaeva (Journal of Intensive Care Medicine, 2026)
Background and Objective The aim of the study was to evaluate the multilevel impact of antenatal prophylaxis and modern non-invasive respiratory strategies on the course and outcomes of respiratory distress syndrome in new-borns. Methods A total of 4080 hospitalisations of preterm and full-term infants with confirmed respiratory failure, born between 1 January 2017 and 30 September 2024, who received care at the Osh Regional Clinical Maternity Hospital (Kyrgyzstan), were included in the retrospective cohort registry. Gestational age, body weight, completeness of the antenatal glucocorticoid course, method of respiratory support, surfactant administration technique, incidence of bronchopulmonary dysplasia, and mortality were analysed. Results Over the observation period, the number of completed courses of betamethasone or dexamethasone increased from 120 to 442, and the proportion of early support with continuous positive airway pressure rose from 24% to 56%. In 2024, minimally invasive surfactant administration via thin catheter was applied in 70% of cases, which was accompanied by a reduction in the mean duration of mechanical ventilation from 68 ± 18 to 36 ± 12 h (p < 0.01) and a decrease in the incidence of bronchopulmonary dysplasia among infants weighing